Art after its end: notes on the “death of art” today - Vercellone, Federico (Religija ir kultūra, 2011)
The on-going debate on the “end” or the “death” of art has continued for almost two centuries. The death we are dealing with in this case is, certainly, a symbolical one, a kind of death (or of murder) that is very frequent in the 19th century. Besides the “death of art”, the ones to mention are also the “death of man” (Max Stirner, Fiodor Dostojevskij) and the “death of God” (Friedrich Nietzsche). These symbolical deaths are very particular as they produce the resurrection of the deceased. For example, after the Hegelian diagnosis of the “end of art”, two very plentiful centuries of artistic production have begun. One can even speak about our time as an epoch dominated by image. Our thesis is that Georg Wilhelm Friedrich Hegel could have seen only a part of the problem. We agree with him as he had spoken reasonably about the “end of art” in relation to the “aesthetic” art, in relation to its possibility to dominate the culture of the present. Nevertheless, we have to recognize that today the new technologies open a new chance for the presence of art in our life. Considering this emergence, we can speak of a return of the “public art”, of the art that is inserted in our daily existence.